Al-Qur'an Memorization Learning Strategy in Forming the Character of Students at the Al-Jihad Student Islamic Boarding School in Surabaya - Muhaimin , Mohammad; El-Yunusi, M. Yusron Maulana (Civiliza Publishing, 2024)
Promiscuity, violent crime, corruption, manipulation, fraud, and other disgraceful acts are some examples of the daily lives of people who have lost their morals. This shows bad behavior and despicable morals. The Arabic term